Analisis Penerapan Sistem Pengendalian Intern (Studi Kasus: Pemerintah Kabupaten Bungo) - Pratiwi, Widya (Jurnal Ekonomi, 2012)
Referring to the minister of home affairs regulation No. 13 of 2006 that any remedy authorized SKPD independently manage financial resources and operational activities including planning, budgeting, administration, accounting, reporting, and accountability areas. This researc aimed to understand the implementation of the internal control system in Bungi Regency Government, to understand the contrains faced in the implementation of the internal control system in Bungo Regency Govenrment, and to obtain an understanding of the efforts made in implementing internal control systems in Bungo Regency Govenrment. This research is a descriptive study with a qualitative epproach. Overall, the implementation and application of the internal control system in Bungi was in quite a performance level value of 49.12%. These result obtained from the sum of the five elements in internal control system: (1) 55,57% of the control environment, (2) risk assessment by 50%, (3) control activities by 44,44%, (4) information and communication amounted to 41,07%, and (5) monitoring of 54,54%. Assessment of the implemnetation of the SPI is quite significant in assessing the potential and shortcomings in the implementation of the elements of the internal control system. The internal control system in Bungo still has many short comings in the implementation, this can be seen from the result of assessments totaliting 49,12%, although this figure is enough overall, but for the details of each element of the internal control it is known that many weaknesses that need attention from the Government Bungo.